Determinants of Jaundice Among Neonates Admitted to Neonatal Intensive Care Unit of Mizan Tepi University Teaching Hospital, Southwest Ethiopia, 2021: Unmatched Case Control Study - Amanuel Adugna MSc; Demekech Ado BSc (SAGE Publishing, 2023)
Background. Jaundice is a common problem in the neonatal period, and it is one of multiple factors found in children who die. Despite the majority of pathological jaundice public health consequences, there is no evidence on risk factors of pathological jaundice among neonates in Southwest Ethiopia. Therefore, this study aimed to identify factors associated with jaundice requiring phototherapy management in neonates admitted to the neonatal unit of a university teaching hospital in Southwest Ethiopia (Mizan-Tepi). Methods. Facility-based, unmatched case-control study was conducted among 240 (80 cases and 160 controls) in the Neonatal Intensive Care Unit of Mizan-Tepi University Teaching Hospital. Neonates with pathological jaundice and neonates without pathological jaundice were considered as cases and controls, respectively. Data were collected using a structured questionnaire, and extraction checklist, including information on maternal demographics, obstetrics, and neonatal factors. Simple random sampling techniques were used to select respondents. Bivariate and multivariable analyses were used to examine the association. Finally, statistical significance was declared at a P -value < .05. Results. In this study, 237 mothers with their neonates were included, making a response rate of 98.7%. The mean birth weight of cases and controls was 2330.3 ± 698.9 and 2699.3 ± 686.7 g, respectively. Hypothermia (AOR = 4.28; 95% CI: [1.72-10.67], cesarean delivery (AOR = 4.09; 95% CI: [1.69-9.93]), breast milk feeding (AOR = 2.97; 95% CI: [1.04-8.47]) and being male (AOR = 2.67; 95% CI: [1.17-6.13]) were significantly associated with jaundice. Conclusion. Most of the risk factors of neonatal jaundice were found to be modifiable. Therefore, early prevention and recognition of identified factors are recommended.